PEMBERDAYAAN MASYARAKAT DALAM PERSPEKTIF PENDIDIKAN ISLAM - Najahah Najahah (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2016)
Conceptually, education based community is a model of education provision which is based on the principle of community, by community and to community. Education of community means education providing the answers of communities' needs. Education by community means society is placed as the subject or the educational actors, not the objects of education. In this context, communities are demanded their role and active participation in any educational program. Indonesian society is muslims majority, so Islamic Education is needed in order to implement Islamic values ​​in everyday life. The human empowerment in Islamic education perspective is through Islamic boarding school education, Da'wah Islamiyah, the assembly of study groups, the establishment of foundations or Islamic organizations, with the levels of RA, MI, MTs, MA, Islamic Education in the family or the worship places, Al-Qur'an education institutions of TPA or TPQ, and other Institutions.